Bank recapitalization and economic recovery after financial crises - Homar, Timotej; van Wijnbergen, Sweder J.G. (Journal of Financial Intermediation, 2017)
Does support to distressed banks early on during financial crises mitigate the macroeconomic consequences of financial distress, and if so does it matter what form the intervention takes? We analyze the effects of government and central bank interventions in 69 systemic banking crises since 1980, of which 29 are part of the recent global financial crisis. Our estimation approach controls for the correlation between intervention measures and the time-invariant component of unobservable crisis severity. We find that timely bank recapitalizations substantially reduce the duration of recessions, underscoring the distortions caused by zombie banks and the costs of regulatory forbearance.